PALM OIL-BASED POLYMER GEL FOR WATER SHUTOFF APPLICATION IN LOW-TEMPERATURE RESERVOIRS - ABDUL FADIL, NURHAZWANE (2021)
Excessive water production has become one of the major problems in the mature oilfield. To mitigate this issue, polymer-based gel technique of the chemical method is favoured compared to the mechanical method due to its various advantages such as wide application in reservoirs and adjustable chemical properties. Currently, polymer with the less environmental effect is highly preferred over conventional polymer. The performance of palm oil-based polyurethane as a water shutoff agent was studied. The monomer used to synthesize palm oil-based polyurethane is methylene diphenyl diisocyanate (MDI) and palm oil-based polyol. The functional groups of gel’s structure and its thermal stability were characterized via Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). Its gelation behaviour in term of gelation time and gel strength were studied. A sandpack flow experiment was run to evaluate the capability of the polymer in reducing permeability towards excessive water. The results showed that palm oil-based polyurethane in the presence of brine was successfully synthesized by showing a similar pattern of FTIR peak as pure polyurethane except for the shifted peak at 1666 cm-1 due to the water adsorption. Meanwhile, its gelation time was significantly affected by NCO/OH molar ratio, temperature and salinity. This polymer exhibited good gel strength after 28 days of ageing time with a higher modulus value compared to the conventional polymer. The reduction permeability percentage and water residual resistance factor showed a good value at 85% and 6.5, respectively. The study concluded that the gelation behaviour of palm oil-based polyurethane can be controlled by varying NCO/OH ratio, salinity, and temperature. Moderate energy is needed to activate its gelation; hence it is suitable to be applied in low-temperature reservoirs. Hence, this study proved the capability of palm oil-based polyurethane to mitigate excessive water production in the oilfield.